The role of Bohdan Khmelnitsky in the formation of the Ukrainian national idea in scientific researches of O. I. Gurzhii, V. S. Smolii and V. S. Stepankov in the early 1990s - Stepanchuk, Yuri (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Introduction. In the early 1990s Ukraine badly needed historical evidence and scientific substantiation of the presence of the own state-building and historical tradition. The threat was obvious that society could be "thrown" by doubts or belief about its absence until 1991. In particular, V. S. Smolii established that the claims had appeared far from historical truth about the nature and course of the National revolution under the leadership of B. Khmelnytsky and explanation of the circumstances of the transition of Ukraine under the protectorate of the Russian Tsar. According to the historian, far from being innocent, as at first glance, attempts can counter the fundamental, objective and deep scientific study of the historical past of Ukraine in all its ambiguity and controversy. Purpose. The purpose of this article is to determine the place and role of scientific works of O. I. Hurzhii, V. S. Smolii and V. S. Stepankov in shaping the modern image of hetman B. Khmelnytsky as an example of the national-building of the mid of XVII century. Methods. The problem-chronological method took the leading place in the writing of this article to cause the structural building of research. It enabled with due fullness to show the place and role of the scientific works of O. I. Hurzhii, V. S. Smolii and V. S. Stepankov in strengthening of the Ukrainian national idea in the early 1990s. Results. On the brink of 1980s–1990s O. I. Hurzhii, V. S. Smolii and V. S. Stepankov became the initiators and participants of the many scientific conferences and «round tables». As a result, not only a strategy of new scientific interpretations of events related with the history of the Cossacks, National liberation revolution and its leader B. Khmelnytsky was produced, but also strong foundation for recovery of State historiography school in Ukraine was laid. On one of the meetings V. S. Smolii urged all the participants to abandon the traditional performances and suggested to pay attention on the study of the problem. The scientist described the negative consequences of the so-called dead season period in the study of problems of feudalism. V.A. Stepankov called the Ukrainian Cossack Republic as a unique state formation on the European continent and stressed the advisability of the creation of the Institute of history of the AN USSR of individual sector of study the history of Ukrainian Cossacks. The declaration of State sovereignty has become the culmination step on the difficult way of the Ukrainian state-building. O. I. Hurzhii, V. S. Smolii and V. S. Stepankov are working on the national concept of the revolutionary events of the middle of XVII century and reproduction of state-building image of B. Khmelnytsky. Originality. It is proved that the state-building image of B. Khmelnitsky created by O. I. Hurzhii, V. S. Smolii and V. S. Stepankov became the one of the symbols of rights heritage of Ukraine-Hetmanshchyna and the young Ukrainian State. Conclusion. At the beginning of the 1990s O. I. Hurzhii, V. S. Smolii and V. S. Stepankov created a fundamental historiography base and contributed to the rapid growth of the number of the latest historical research dedicated to B. Khmelnytsky and events of Ukrainian national revolution of the mid of XVII century that became proportional to the growth of national and state identity of Ukrainian society.